Lacticaseibacillus rhamnosus Glory LG12 preventives loperamide-induced constipation in mice by modulating intestinal flora and metabolic pathways - Ma, Weiwei; Lian, Lian; Guo, Lidong; Wu, Yanan; Huang, Lili (Frontiers in Microbiology, 2025)
IntroductionConstipation is a common gastrointestinal disease, the incidence of which has been increasing year by year in recent years, and prolonged constipation seriously affects the physical and mental health of patients. Constipation often leads to dysbiosis of the intestinal flora, which in turn exacerbates intestinal dysfunction, and this may be an important mechanism for the development of constipation. Studies have shown that probiotics may be effective in relieving constipation by regulating intestinal flora. Among them, Lacticaseibacillus rhamnosus Glory LG12 (L. rhamnosus Glory LG12), as a potential probiotic strain, has attracted much attention in regulating intestinal flora and improving intestinal function. Although it has shown potential in the treatment of gastrointestinal disorders, its specific role in the treatment of constipation and the related mechanisms are unknown and require in-depth study.MethodsIn the present study, a mouse model of constipation was constructed by loperamide hydrochlorid. The effect and mechanism of L. rhamnosus Glory LG12 on constipation were investigated by the indicators of water content of defecation, small intestine transit rate, time to the first black stool, defecation and number of grains in 5 h defecation, colonic pathology, inflammatory factors, neurotransmitters, short-chain fatty acids (SCFAs), intestinal flora and other indicators.ResultsThe results showed that L. rhamnosus Glory LG12 could prevent constipation symptoms to a great extent, and the preventive effect on constipation was more significant with the increasing dose of L. rhamnosus.DiscussionThe mechanism of action may be related to the up-regulation of the abundance of Bacteroidota, Firmicutes, Bacteroides, Ligilactobacillus and Parabacteroides in the intestinal flora, the biosynthesis of amino acids, pyrimidine metabolism and other metabolic pathways, the promotion of a variety of glycoside hydrolases, and the increase of short-chain fatty acid content in the defecation of constipated mice.